Electron transport layer assisted by nickel chloride hexahydrate for open-circuit voltage improvement in MAPbI3 perovskite solar cells. Issue 22 (9th May 2022) - Dong, Pei; Yuan, Shuai; Zhu, Dongping; Du, Yaxin; Mu, Cheng; Ai, Xi-Cheng
Abstract : Nickel chloride hexahydrate (NiCl2 ·6H2 O) was introduced into the SnO2 ETL, which significantly increased open-circuit voltage ( V OC ) and power conversion efficiency (PCE) Abstract : SnO2 is a promising electron transport layer (ETL) material with important applications in planar perovskite solar cells (PSCs). However, electron–hole recombination and charge extraction between SnO2 and the perovskite layer necessitates further exploration. Nickel chloride hexahydrate (NiCl2 ·6H2 O) was introduced into the SnO2 ETL, which significantly increased the power conversion efficiency (PCE) from 15.49 to 17.36% and the open-circuit voltage ( V OC ) from 1.078 to 1.104 V. The improved PCE and V OC were attributed to the reduced defect states and increased energy level of the conduction band minimum. This work provides new insights into optimizing the V OC and PCE of PSCs.